Dampak β-Hidroksibutirat (BHB) pada Tubuh Manusia: Tinjauan tentang Badan Keton, Sumber, Metabolisme, Manfaat Kesehatan, dan Kerugian Potensial - Muhammad Raka Tresna; Hadi Sudarjat (Poltekkes Kemenkes Padang, 2024)
Ketone bodies are small lipid-derived molecules that have a function as a circulating energy source for tissues when in glucose deficiency conditions. When glucose in glycogen stores is largely depleted, fatty acid breakdown will occur in the mitochondria through β-oxidation which produces ATP and acetyl-CoA. Fatty acid breakdown in the liver will produce ketone bodies, which then reduce acetoacetate to β-hydroxybutyrate (BHB) that serves as alternative energy. The purpose of this study is to determine the impact of β-hydroxybutyrate (BHB) used in the form of supplements on the body and as an alternative energy source, is expected to provide insight into the impact of β-hydroxybutyrate (BHB) on the body. The method used is a qualitative method using narrative literature review on 5 articles that have been analyzed, and meet the eligibility of 2306 articles found on PubMed between 2014 and 2024. The results of this study β-hydroxybutyrate (BHB) has good effectiveness and safety for the body and is good as an alternative energy source, and has no negative impact on health. The conclusion of this study is that supplementing the body with ketones supports the effectiveness of ketone bodies to provide alternative energy and better resilience. It is recommended that researchers who will take the title of research on β-hydroxybutyrate (BHB) to see the potential given to health and its usefulness in having an impact on the body.